Current status of transcatheter mitral valve replacement: systematic review and meta-analysis - Alberto Alperi; Alberto Alperi; Pablo Avanzas; Pablo Avanzas; Pablo Avanzas; Victor Leon; Iria Silva; Daniel Hernández-Vaquero; Daniel Hernández-Vaquero; Daniel Hernández-Vaquero; Marcel Almendárez; Marcel Almendárez; et al. (Frontiers in Cardiovascular Medicine, 2023)
IntroductionMitral Regurgitation (MR) has a strong impact on quality of life and on mid-term survival. Transcatheter mitral valve replacement (TMVR) is rapidly expanding and a growing number of studies have been published recently.MethodsA systematic review of studies reporting on clinical data for patients with symptomatic severe MR undergoing TMVR was performed. Early- and mid-term outcomes (clinical and echocardiographic) were evaluated. Overall weighted means and rates were calculated. Risk ratios or mean differences were calculated for pre- and post-procedural comparisons.ResultsA total of 12 studies and 347 patients who underwent TMVR with devices clinically available or under clinical evaluation were included. Thirty-day mortality, stroke and major bleeding rates were 8.4%, 2.6%, and 15.6%, respectively. Pooled random-effects demonstrated a significant reduction of ≥ grade 3+ MR (RR: 0.05; 95% CI: 0.02–0.11; p < 0.001) and in the rates of patients in NYHA class 3–4 after the intervention (RR: 0.27; 95% CI: 0.22–0.34; p < 0.001). Additionally, the pooled fixed-effect mean difference for quality of life based on the KCCQ score yielded an improvement in 12.9 points (95% CI:7.4–18.4, p < 0.001), and exercise capacity improved by a pooled fixed-effect mean difference of 56.8 meters in the 6-minute walk test (95% CI 32.2–81.3, p < 0.001).ConclusionsAmong 12 studies and 347 patients comprising the updated evidence with current TMVR systems there was a statistically significant reduction in ≥ grade 3+ MR and in the number of patients exhibiting poor functional class (NYHA 3 or 4) after the intervention. Overall rate of major bleeding was the main shortcoming of this technique.